Microstructure and Properties of Ion Permeated W - Ni - Al Alloy on Tungsten Surface for Power Switch - SUN Xi-bao, ZHAI Wen-sheng (Cailiao Baohu)
For improving the friction and corrosion resistance of tungsten alloy for power switch, W-Ni-AL coatings were prepared on the surface of sample substrate by double luminescence infiltration, and the difference of tungsten surface performance under different coating structures formed was compared by experimental tests. Results showed that there were dense structures formed in the coating, and almost no crack was observed. After increasing the metallization temperature, the thickness of coatings increased continuously. Meantime, the coating contained WNi2Al3 and NiW2. When the surface was covered by the W-Ni-Al coating, the hardness increased significantly. With the improvement of the load, the hardness began to decrease. Overall, the friction coefficient of W-Ni-Al coating was higher than that of substrate. At 1 150 ℃, the coating obtained the minimum volume wear rate, only 13.6% of the substate, showing excellent wear resistance. Besides, the microstructure of the coating was fractured, and grooves in parallel sliding direction were formed on the surface of the grinding mark. Compared with the substrate, the corrosion potential of the coating shifted to positive significantly, the corrosion current density decreased greatly, which indicated that the coating possessed better corrosion resistance.